2012
DOI: 10.4034/pboci.2012.124.20
|View full text |Cite
|
Sign up to set email alerts
|

Edentulismo, Uso e Necessidade de Prótese e Fatores Associados em Município do Nordeste Brasileiro

Abstract: Introdução: No Brasil, a população idosa cresce com o aumento da expectativa de vida constituindo uma responsabilidade para os gestores públicos na perspectiva de uma oferta de atenção adequada com conhecimento epidemiológico para o planejamento efetivo de políticas públicas. Para a saúde bucal o mais importante indicador para essa população é o edentulismo. Objetivo: Testar a associação entre os desfechos edentulismo/uso e necessidade de prótese dentária e dados sociodemográficos e de acesso em adultos e idos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
4
1
7
Order By: Relevance
“…Most dental prosthesis used were removable (partial and/or denture). These results may be in contrast with other studies also conducted in Brazil 9,20,21 . The last national oral health survey showed that only 54% of the elderly used dental prosthesis 22 .…”
Section: Discussioncontrasting
confidence: 96%
“…Most dental prosthesis used were removable (partial and/or denture). These results may be in contrast with other studies also conducted in Brazil 9,20,21 . The last national oral health survey showed that only 54% of the elderly used dental prosthesis 22 .…”
Section: Discussioncontrasting
confidence: 96%
“…This is confirmed when full tooth loss (edentulism) is seen as a normal and natural phenomenon that occurs with aging rather than the result of lack of health preventive policies aimed at the adult population for maintenance of teeth until advanced ages 14,16,19 . This long-standing dental paradigm of edentulism has been improving over the years as people are increasingly conserving their natural teeth, and this is directly associated with the socioeconomic and cultural conditions of the population [19][20][21] .…”
Section: Methodsmentioning
confidence: 59%
“…Sin embargo, en algunos casos las necesidades protésicas se debían a la falta de retención y/o adaptación de la prótesis. Medeiros y col., realizaron un estudio en una población adulta entre las edades de 35 a 74 años, encontrando que la necesidad de prótesis para el maxilar superior fue de 62% y para el maxilar inferior de 91% (14). Así mismo, Netto y col., observaron que la necesidad de prótesis estaba presente en la población estudiada en 56,6% para ambos maxilares (15).…”
Section: Discussionunclassified